2016
DOI: 10.1371/journal.pone.0152458
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and White Blood Cell Counts Response to Environmental Levels of Diesel Exhaust and Ozone Inhalation Exposures

Abstract: Epidemiological observations of urban inhalation exposures to diesel exhaust (DE) and ozone (O3) have shown pre-clinical cardiopulmonary responses in humans. Identifying the key biological mechanisms that initiate these health bioindicators is difficult due to variability in environmental exposure in time and from person to person. Previously, environmentally controlled human exposure chambers have been used to study DE and O3 dose-response patterns separately, but investigation of co-exposures has not been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 52 publications
(51 reference statements)
1
31
0
2
Order By: Relevance
“…This is in part comparable to a laboratory‐based exposure study in which mice intratracheally instilled with motorcycle exhaust particles induced a Th2 response and airway eosinophilia . In addition, our findings are consistent with numerous previous studies showing increased overall inflammation including neutrophilia in the airways of experimental animals and humans following TRAP exposure.…”
Section: Discussionsupporting
confidence: 91%
“…This is in part comparable to a laboratory‐based exposure study in which mice intratracheally instilled with motorcycle exhaust particles induced a Th2 response and airway eosinophilia . In addition, our findings are consistent with numerous previous studies showing increased overall inflammation including neutrophilia in the airways of experimental animals and humans following TRAP exposure.…”
Section: Discussionsupporting
confidence: 91%
“…These include localized effects such as bronchoconstriction and increased airway resistance, [ 23,50,51 ] pulmonary inflammation, [ 23,52–59 ] and oxidative stress, [ 50,55,60 ] DNA methylation in bronchial biopsies or blood cells, [ 61,62 ] and exacerbation of allergic responses [ 63 ] as well as reductions in parameters related to exercise capacity. [ 64 ] Systemic effects have also been analyzed such as inflammation [ 52,65–67 ] and oxidative stress, [ 68–70 ] increased levels of circulating oxidized lipoprotein receptors, [ 71 ] increased blood pressure, [ 72 ] impaired vascular function (arterial contraction), [ 73,74 ] reduced vasodilator responses, [ 75–79 ] increased arterial stiffening, [ 80 ] promotion of blood clotting, [ 69,81 ] and increased cardiac ischaemia [ 82 ] ( Figure ). Experiments that removed the particulate fraction of DE using experimental filtering or exhaust particle traps [ 83,84 ] demonstrated that it was the particulate constituents of DE that drive cardiovascular impairments.…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%
“…In essence, sample source and cell type heterogeneity (i.e., human genetic heterogeneity) are problematic in epigenomic studies because human samples often consist of blood (owing to ease of access) that is composed of mixed cell types. Each cell type has a unique epigenetic profile, and the relative proportion of each cell type in a sample may vary as a result of exposure ( Stiegel et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%